2021
DOI: 10.1002/onco.13752
|View full text |Cite
|
Sign up to set email alerts
|

FDA Approval Summary: Atezolizumab and Durvalumab in Combination with Platinum-Based Chemotherapy in Extensive Stage Small Cell Lung Cancer

Abstract: The U.S. Food and Drug Administration (FDA) granted approval to atezolizumab and durvalumab in March of 2019 and 2020, respectively, for use in combination with chemotherapy for first-line treatment of patients with extensive stage small cell lung cancer. These approvals were based on data from two randomized controlled trials, IMpower133 (atezolizumab) and CASPIAN (durvalumab). Both trials demonstrated an improvement in overall survival (OS) with anti-PD-L1 antibodies when added to platinum-based chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 10 publications
0
80
0
1
Order By: Relevance
“…The NCCN SCLC Panel recommends (category 1) durvalumab plus etoposide plus (carboplatin or cisplatin) as a preferred firstline systemic therapy option followed by maintenance durvalumab for patients with extensive-stage SCLC based on clinical trial data and the FDA approval (see SCL-E 1, page 1450). 86,[89][90][91] Other Primary Systemic Therapies Other recommended regimens for extensive-stage SCLC include etoposide with either cisplatin or carboplatin (see SCL-E 1, page 1450). Before the recent favorable data on immunotherapy, many other chemotherapy combination regimens had been evaluated in patients with extensive-stage disease with little consistent evidence of benefit compared with EP.…”
Section: Scl-e 3 Ofmentioning
confidence: 99%
“…The NCCN SCLC Panel recommends (category 1) durvalumab plus etoposide plus (carboplatin or cisplatin) as a preferred firstline systemic therapy option followed by maintenance durvalumab for patients with extensive-stage SCLC based on clinical trial data and the FDA approval (see SCL-E 1, page 1450). 86,[89][90][91] Other Primary Systemic Therapies Other recommended regimens for extensive-stage SCLC include etoposide with either cisplatin or carboplatin (see SCL-E 1, page 1450). Before the recent favorable data on immunotherapy, many other chemotherapy combination regimens had been evaluated in patients with extensive-stage disease with little consistent evidence of benefit compared with EP.…”
Section: Scl-e 3 Ofmentioning
confidence: 99%
“…The CASPIAN study tested another PD-L1 inhibitor, durvalumab, in combination with etoposide and platinum. In this study, there was statistical benefit to adding durvalumab to first-line treatment, with patients receiving durvalumab, etoposide and platinum achieving an overall survival of 13.0 months compared to 10.3 months in the control arm (Mathieu et al, 2021). In March 2020, the US FDA approved durvalumab in combination with etoposide and either carboplatin or cisplatin as first-line treatment of patients with extensive-stage small cell lung cancer.…”
Section: Immunotherapy Increases Survival In Sclcmentioning
confidence: 82%
“…Atezolizumab, when added to first line carboplatin and etoposide, improves overall survival. The IMpower33 study showed that patients receiving atezolizumab, carboplatin and etoposide had a median overall survival of 12.3 months compared to 10.3 months in the control group ( Mathieu et al, 2021 ). Progression free survival was also statistically improved, with a PFS of 5.2 months in the experimental arm compared to 4.3 months in the control arm ( Mathieu et al, 2021 ).…”
Section: Immunotherapy Increases Survival In Sclcmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, complete tumor regression has been observed in some NSCLC (20)(21)(22) and SCLC (23)(24)(25) patients treated with chemo-immunotherapy. Atezolizumab and durvalumab are also approved in combination with platinum-based chemotherapy for advanced SCLC patients (26). However, these best-case responses are only observed in a minority of patients.…”
Section: There Is An Urgent Need To Develop Biomarkers Of Response To Immune Checkpoint Blockadementioning
confidence: 99%